If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x+12+5x=2(8x+8)
We move all terms to the left:
10x+12+5x-(2(8x+8))=0
We add all the numbers together, and all the variables
15x-(2(8x+8))+12=0
We calculate terms in parentheses: -(2(8x+8)), so:We get rid of parentheses
2(8x+8)
We multiply parentheses
16x+16
Back to the equation:
-(16x+16)
15x-16x-16+12=0
We add all the numbers together, and all the variables
-1x-4=0
We move all terms containing x to the left, all other terms to the right
-x=4
x=4/-1
x=-4
| x(x+32)=0 | | 3c—3(6-2c)=27 | | 4(x-3)-x=1x-6 | | n/2=2n*3 | | -2x-3=-8x+3 | | 23-(-3r)=-10 | | 1.15(2p+1.50=11.50 | | x=8.15x-2= | | 5x-10=2x-60 | | +10+3w=-43 | | z/5-5=21)4 | | x=90+1/1.1862068965519 | | 9/x=6/15 | | -10x+2=-42 | | 1/3x+4/9=5 | | -12-2(x+1)=5x= | | 6m=m+40 | | x=90+3.22222222222/3.82222222222 | | -3x-9=-x-1 | | |h-8|=10 | | -3=-3x-(x+9) | | 5(x-2)=12x-70 | | n/2=2n(3) | | 2x–16=x+38 | | -13+25=-4(x+6) | | 2x=90+x) | | 2.5x+0.8=4.6-1.3 | | 16t+24=-4t+64 | | 5x-10=12x-70 | | -3=-3x-(x-9) | | -15=2p | | 2=-17-x |